Ferulic acid confers protection on islet Î² cells and placental tissues of rats with gestational diabetes mellitus - Zhao, Jian; Gao, Jianrong; Li, Huan (Cellular and Molecular Biology, 2020)
Gestational diabetes mellitus (GDM) refers to glucose intolerance of variable degree with onset or first recognition during pregnancy. It causes polyhydramnios, ketoacidosis, fetal macrosomia, and neonatal respiratory distress syndrome. The incidence of GDM has greatly increased, hence the search for new interventions that can effectively treat it. The present study investigated the protective effect of ferulic acid on islet Î² cells and placental tissues of rats with GDM. Female Sprague Dawley rats (n = 30) were used in this study. The rats were randomly assigned to three groups of 10 rats each: control group, GDM group and ferulic acid group. The rats were fed high-fat diet consecutively for 12 weeks, except those in control group. In addition, ferulic acid group rats received ferulic acid at a dose of 20 mg/kg body weight (bwt) intragastrically daily for 12 weeks. The expressions of insulin signal transduction proteins and inflammatory factors were determined in rat placental tissue. Apoptosis and levels of expression of apoptosis-related proteins were assessed in isolated islet Î² cells. The results showed that the expressions of p-IRS1, p-IRS2, p-PI3K, GLUT1, GLUT3, and GLUT4 were significantly reduced by GDM, but were significantly upregulated after treatment with ferulic acid (p < 0.05). The levels of expression of NF-kB, ICAM-1, TNF-Î± and IL-Î² in placental tissues were significantly higher in GDM group than in control group, but were significantly reduced by ferulic acid treatment (p < 0.05). However, the protein expression of visfatin was significantly reduced by GDM, but was significantly increased by ferulic acid treatment (p < 0.05). Apoptosis was significantly promoted by GDM in islet Î² cells, but was significantly and concentration-dependently reduced after treatment with ferulic acid (p < 0.05). Gestational diabetes mellitus (GDM) also significantly down-regulated the expression of bcl-2, but markedly upregulated the expressions of bax and caspase-3 (p < 0.05). However, treatment with ferulic acid significantly and concentration-dependently upregulated the expression of bcl-2, but down-regulated bax and caspase-3 protein expressions (p < 0.05). These results indicate that ferulic acid protects Î² cells from GDM-induced apoptosis and improves insulin signaling in placenta of female rats with GDM.